Translation, cross‐cultural adaptation and validation of the “Cardiff wound impact schedule,” a wound‐specific quality of life instrument, to the native Spanish of Mexican patients - Lozano‐Platonoff, Adriana (Int Wound J, 2019)
The aim of this study was to translate into Mexican Spanish, cross‐culturally adapt and validate the wound‐specific quality of life (QoL) instrument Cardiff wound impact schedule (CWIS) for Mexican patients. This instrument went through the full linguistic translation process based on the guidelines of Beaton et al (Beaton DE, Bombardier C, Guillemin F, Ferraz MB, Guidelines for the process of cross‐cultural adaptation of self‐report measures, Spine Phila Pa, 1976, 2000, 318‐391). We included a total of 500 patients with chronic leg ulcers. The expert committee evaluated the Face validity and they agreed unanimously that the instrument was adequate to assess the QoL of these patients, covering all relevant areas presented by them. The content validity index obtained was of 0.95. The construct validity demonstrated moderately significant correlations between related sub‐scales of CWIS and SF‐36 (P = .010 to P < .001). The instrument was able to discriminate between healed and unhealed ulcers. The instrument obtained an overall Cronbach's alpha of .952, corresponding to an excellent internal consistency (.903‐.771 alpha range for domains). The CWIS can be appropriately used to assess the health‐related QoL of Mexican patients with chronic leg ulcers.